2021
DOI: 10.1136/jim-2020-001688
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a new predictive model with other critical scores for predicting in-hospital mortality among children with pneumonia-related bacteremia

Abstract: Prediction of mortality in children with pneumonia-related bacteremia is necessary for providing timely care and treatment. This study aims to develop and validate a nomogram and compare it with Pediatric Risk of Mortality III (PRISM III), Brighton Pediatric Early Warning Score (Brighton PEWS) and Pediatric Critical Illness Score (PCIS), which are widely used in predicting in-hospital mortality in children with pneumonia-related bacteremia. This retrospective study collected clinical data of hospitalized child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Consistent with previous studies, the present study found that PCIS was a vital risk factor for SAE development in children with sepsis. Moreover, the PCIS showed good accuracy and discriminatory ability in the prognostic prediction of many other critical diseases, such as pneumonia-related bacteremia, hand-foot-and-mouth disease, acute paraquat poisoning, and acute leukemia [ 36 39 ]. However, data on the correlation between PCIS and SAE are limited, and future high-quality studies are needed for further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous studies, the present study found that PCIS was a vital risk factor for SAE development in children with sepsis. Moreover, the PCIS showed good accuracy and discriminatory ability in the prognostic prediction of many other critical diseases, such as pneumonia-related bacteremia, hand-foot-and-mouth disease, acute paraquat poisoning, and acute leukemia [ 36 39 ]. However, data on the correlation between PCIS and SAE are limited, and future high-quality studies are needed for further exploration.…”
Section: Discussionmentioning
confidence: 99%